The Implementation of Interactive Multimedia in Encouraging Students' Participation in Distance Learning - Reyvione Ndun, Chika; Datu Appulembang, Oce (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
The Covid-19 pandemic has necessitated schools to conduct distance learning. Teachers and students do not have face-to-face interactions in the classroom. Schools have implemented policies to reduce instructional hours. Teachers and students have had to adapt to these conditions. Christian education views students as creations of God, made in His image and likeness. Students are created by God with different abilities and uniqueness. Teachers play the role of facilitators in the classroom, preparing interactive teaching materials, methods, and learning media. Students participate by providing responses, asking questions, giving opinions in discussions, and being able to follow instructions and rules during the learning process. During teaching practice, there was an issue of low student participation. The purpose of this writing is to describe the use of interactive learning media that can encourage active student participation during remote learning. The research method used is descriptive qualitative. Interactive learning media has an impact on the level of student participation. The design of interactive multimedia includes features such as images, sound, graphics, video, and animation that can capture students' attention. When combined with good content, this media design can enhance student participation. Teachers need to pay attention to students' needs, uniqueness, and potential. Teachers should learn to use technology in designing interactive learning media. The design of interactive learning media should be done with careful preparation.